Evaluation of the efficiency of Trichogramma lopezandinensis (Hymenoptera: Trichogrammatidae) to control Tocia solaniuora (Lepidoptera: Gelechiidae) in storage potato - RUBIO-C., SILVIA ALEJANDRA; VARGAS-A., BLANCA IRENE; LÓPEZ-ÁVILA, ARISTÓBULO (Revista Colombiana de Entomología, 2004)
The efficiency of the parasitoid Trichogramma lopezandinensis Sarmiento to control the Guatemalan potato tuber moth Tecia solanivora (Povolny) in stored potato was evaluated. Four experiments were carried out to determine biological aspects of their interaction at three trophic levels constituting the stored potato, the pest and the parasitoid. These experiments included the design of a device to release the parasitoid, determination of the densities and frequencies of parasitoid release required to prevent damage of the pest and effect of light on the parasitic activity of the wasp. The study was conducted at the Research Center Tibaitatá, in the IPM program of Corpoica, and was conducted under controlled conditions of temperature, humidity and light. The experimental unit consisted of a wooden cage with muslin walls, in which a tray was introduced with 100 tubers, of an average 100 g each. An efficient device to release the parasitoid in storage conditions was designed and implemented which was denominated the "tunnel type". lt was found that light conditions are an important factor in the parasitic activity of the wasp, presenting the highest percentages of parasitism under normal light conditions in the laboratory compared to complete darkness. In the experiments of densities and frequencies of parasitoid release, it was found that frequency is a significant factor in preventing of damage caused by the pest. Frequency of release every three days showed the best results. indicating that the continuous presence of young females is critica) for achieving better parasitism.